2015
DOI: 10.4161/19420862.2015.989013
|View full text |Cite
|
Sign up to set email alerts
|

Production of bispecific antibodies in “knobs-into-holes” using a cell-free expression system

Abstract: (2015) Production of bispecific antibodies in "knobs-into-holes" using a cell-free expression system , mAbs, 7:1, 231-242, DOI: 10.4161/19420862.2015.989013 To link to this article: https://doi.org/10. 4161/19420862.2015 Bispecific antibodies have emerged in recent years as a promising field of research for therapies in oncology, inflammable diseases, and infectious diseases. Their capability of dual target recognition allows for novel therapeutic hypothesis to be tested, where traditional mono-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 66 publications
5
54
0
Order By: Relevance
“…Pharmacokinetics studies in rats showed that BEAT antibodies benefited from a prolonged half-life similar to that of previously reported Hc heterodimers (26, 27); for example, an elimination half-life ( t ½ ) of 164 h following i.v. injection of 10 mg/kg of BEAT 2/3 was observed (supplemental Table S2; note that antibody U1-59 has been reported to cross-react with rat HER3 (22)).…”
Section: Resultssupporting
confidence: 79%
“…Pharmacokinetics studies in rats showed that BEAT antibodies benefited from a prolonged half-life similar to that of previously reported Hc heterodimers (26, 27); for example, an elimination half-life ( t ½ ) of 164 h following i.v. injection of 10 mg/kg of BEAT 2/3 was observed (supplemental Table S2; note that antibody U1-59 has been reported to cross-react with rat HER3 (22)).…”
Section: Resultssupporting
confidence: 79%
“…As reconstitution efficiency is highly dependent on antibody fragment concentration and the molar ratio of the two monovalent antibody fragments, it has been reported that purification of product-related impurities is very difficult and remains a manufacturing challenge, especially in small-scale screening applications. [14,36] The method presented herein allows for a one-step purification without elution of the desired antibody due to a His-Tag fusion to each antibody fragment as well as the resulting intein side product. Non-reconstituted antibody fragments and processed intein can be extracted via Ni 2+ beads in 384well format.…”
Section: Discussionmentioning
confidence: 99%
“…To promote heterodimerization of two heavy chains with different specificities, CH3 domains are engineered to bear either a "knob" or a "hole" in each antibody heavy chain by amino acid replacement [122]. Recently, this technology has been applied in an E. coli-based cell-free translation system creating bispecific antibodies in different designs (e.g., two-armed heterodimeric scFv-knobs-into-holes; one-armed assymetric BiTE knobs-into-holes with tandem scFv) [123].…”
Section: Discussionmentioning
confidence: 99%